Fiscal policy effectiveness and neutrality results in a non-Ricardian world - Carsten Detken (European Central Bank (ECB), 1999)
The paper introduces monetary and fiscal regimes into a Blanchard-Weil overlapping generations model. Contrary to intuition, it is shown that fiscal policy becomes more effective, the less the central bank monetises government debt. Furthermore, there is a degree of debt monetisation at which Ricardian equivalence seems to hold in this 'non-Ricardian' model, as fiscal policy is neutral with respect to agent's net wealth. At the origin of these results are the opposite intergenerational wealth effects of money and debt financing. Since, on average, central bank independence increased through EMU, the analysis suggests that fiscal policy might have become a more powerful instrument for euro-area countries. It is further argued that given the Stability and Growth Pact, governments will find it wise to run budget positions 'close to balance or in surplus' in order to maintain the increased fiscal policy effectiveness.
Keywords: E63; 330; fiscal policy effectiveness